NON-INVASIVE DIAGNOSTICS OF LIVER FIBROSIS IN PATIENTS WITH CHRONIC HEPATITIS B AND C - Bokieva Charos Sharofovna; Tilloyeva Shakhlo Shavkatovna (KONFERENSIYALAR, 2025)
Resume. Chronic diffuse liver diseases, especially viral liver damage, are one of the most urgent problems of modern hepatology. The aim of the study was to conduct a clinical assessment using ultrasound Dopplerography and ultrasound elastometry for non-invasive diagnosis of liver fibrosis in patients with chronic hepatitis. In a comparative analysis using non-invasive diagnostic methods to assess the degree of liver fibrosis, ultrasound elastometry is more informative than ultrasound Doppler.